Glass production at an Early Islamic workshop in Tel Aviv. (October 2015) - Freestone, Ian C.; Jackson-Tal, Ruth E.; Taxel, Itamar; Tal, Oren
Abstract: A refuse deposit at HaGolan Street, Khirbet al-Ḥadra, northeastern Tel Aviv, is rich in debris deriving from an Islamic period glass workshop, dating to the 7th–8th centuries. Twenty-four samples of glass vessels, chunks and moils were analysed by electron microprobe. Glass used in the workshop derives from three primary sources: Egypt II, somewhere in inland Egypt, Beth Eli'ezer, near Hadera, Israel and a third group which appears to represent a previously unknown Levantine primary production centre. Glass corresponding to at least twelve production events has been identified. While vessels made of Beth Eli'ezer and Egypt II glass have previously been reported from the same context, this is the first time that they have been related to the products of a single workshop. It appears that glass from both primary production centres was available in the later 8th century, and that the glass workers at HaGolan St were obliged to balance the high working and fuel costs of the stiff low-soda Levantine glass against the better working properties but higher raw material costs of the high-soda glass from Egypt. Highlights: First published example from Palestine of an early Islamic secondary workshop. Co-existence of glass from three primary production centres. Raw glass made in Egypt and glass made in Palestine available to the glassworkers. At least 12 production events identified. Importance of batch analysis for the interpretation of glass workshops.